O eu, o outro e o nós: um caminho para compreender a diversidade na educação física escolar na perspectiva das crianças - Francisco, Cristiane Pereira de Souza (Universidade Federal de São Carlos, 2018)
Throughout its history, Physical Education has divided many people by excluding them from its training as they aim for healthy and strong bodies, due to ideas embedded in its concept. However, as well as the historical context, Physical Education has been changing to fit into this adjustment, which currently requires including “everybody” in its trainings. With this new context, I aimed to understand how Diversity has been addressed in School Physical Education classes; but I aimed to go beyond on what teachers, specialists and renowned authors say about such theme. I aim to consider Diversity from the view of children of the 1st grade of Elementary Scholl and answer to the following question: on the situations experienced in School Physical Education classes: how do they lead children to comprehend the Diversity around them? For them, what Diversity is? How do they live with such Diversity? These are three questions that complement each other within the same research field and that support our target, which is to understand and research Diversity around the universe of children of the 1st grade of Elementary Scholl during the trainings and conversations about School Physical Education. The method used was a qualitative research based on the participant observation and round table, aiming to collect information and carried out in the first semester of 2017 in a state school of Araraquara city. The information gathered with the children lead me to develop three categories, namely: me and the other; the Cultural Diversity around the children’s universe and the Cultural Diversity in Physical Education classes. Therefore, I could realize that, even before the challenge in School Physical Education classes, the Cultural Diversity around the children’s universe is clear in the social markers of diversity, such as skin color, height, weight and gender. In addition to these markers, other dialogues arise in conversations about the differences of race and ethnic relations and relations with special education, gender and religion. I also found that, for the children, Cultural Diversity has several meanings: from fun and playing to differences between people. All that surrounded by interactions that are not always easy to handle, where everybody wants to speak, even if they are not heard. Due to the Cultural Diversity, often their actions are not challenged; for this reason, they freely act to immediately solve questions and to continue playing or talking.
Me, the other and us: a path to comprehend diversity in school physical education from the children’s perspective
Keywords: Crianças; Educação física; Diversidade; Children; Physical education; Diversity; CIENCIAS HUMANAS::EDUCACAO